(untitled) (Experimental biology, 2015)
The work is devoted to study the extracellular matrix component, high molecular weight hyaluronan, on the suppressor activity of CD4+CD25+FoxP3+ Treg cells, which were obtained from healthy human peripheral blood. Hyaluronan has been established to increase suppressor activity of Treg cells in part of donors; in other individuals it caused a decrease in this parameter. Hyaluronan did not influence on the production of IL-10 by Treg cells. In its turn suppressor activity has not been associated with IL-10 production by Treg cells. Some mechanisms of hyaluronan infulence on the suppression by Treg cells are discussed. Experimental approaches worked out in this study, can be useful for investigation of the impaired Treg-dependent immunosupression in pathologic states as autoimmunity and cancer.